Lithium energy storage device with internal fuse
By introducing a thin metallic album in a lithium battery to form an internal fuse, the problem of high temperature and fire caused by the short circuit of lithium batteries is solved, and a safer and reliable battery design is achieved, and the weight and cost are reduced.
Patent Information
- Application Number
- CN202311272715.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-20
- Filing Date
- 2018-09-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2038-09-06
AI Technical Summary
Existing lithium batteries are prone to short circuits, causing high temperatures and fires, and poses safety hazards, especially during manufacturing and use.
Introduce a thin metallic album in a lithium battery to provide an internal fuse on the surface. The oxide of the conductive material is used to form a non -conductive metal oxide to prevent the flow of short -circuit charge and prevent heat out of control.
Effectively prevent the heat out of control caused by short circuits, improve the safety and reliability of lithium batteries, reduce weight and cost, while avoiding ignition of electrolytes.
Smart Images

Figure CN117673368B_ABST
Abstract
Description
[0001] This application is a divisional application of the PCT invention patent application with international application number PCT / US2018 / 049799 filed on September 6, 2018 (entered the Chinese national phase on March 24, 2020, with national phase application number 201880061990.6 and invention name “Lithium energy storage device with internal fuse”). Technical Field
[0002] The present technology relates to improvements in the structural components and physical properties of lithium battery products. For example, standard lithium-ion batteries are prone to certain phenomena related to short circuits and have therefore experienced high temperature occurrences and ultimately combustion. It has been found that structural problems associated with battery components cause such problems. The improvements provided by the present invention include the use of thin metallized current collectors (e.g., aluminum and / or copper), high shrinkage materials, materials that become non-conductive when exposed to high temperatures, and combinations thereof. Such improvements provide the ability to withstand certain defects (dendrites, unexpected surges, etc.) in the target lithium battery itself by providing an internal fuse on the surface within the target lithium battery to prevent adverse high temperature results caused by short circuits. Battery products including such improvements and methods of use thereof are also included in the present invention. Background Art
[0003] Lithium batteries remain popular around the world as a power source in a wide range of products. From rechargeable power tools to electronic cars to ubiquitous cellular phones (such as tablets, handheld computers, etc.), lithium batteries (of different ion types) are used as the main power source due to reliability, the above-mentioned rechargeability and long service life. However, utilizing such a widely used power source brings certain problems, some of which have proven to be increasingly serious. Notably, safety issues have been exposed, in which certain defects in such lithium batteries, whether due to initial manufacturing problems or time-related degradation problems, can cause ignition potentials to be easily generated during short circuit events. Basically, internal defects in the conductive materials have been found to generate undesirably high heat within such battery structures and ultimately cause fires. As a result, certain products using lithium batteries, from handheld computer devices (Samsung Galaxy Note 7, as an infamous case) to entire aircraft (Boeing 787), have been banned from sale and / or use until a solution has been provided for the damaged lithium batteries used therein and therewith (even to the extent of banning the use of Samsung Galaxy Note 7 on any aircraft in certain regions). Even the Tesla line of electric vehicles has experienced notable issues with lithium battery components, which has generated headlines of expensive cars exploding like fireballs due to battery issues. As a result, widespread recalls or outright bans related to such lithium battery issues persist to this day, making it urgent to overcome such issues.
[0004] These problems exist primarily due to manufacturing issues, both in terms of the individual battery components that are made and in terms of how such components themselves are configured into individual batteries. Upon closer inspection, lithium batteries are currently made of six major components: a positive electrode material; a positive electrode current collector (such as aluminum foil) coated with the positive electrode material; a negative electrode material; a negative electrode current collector (such as copper foil) coated with the negative electrode material; a separator located between the negative and positive electrode layers and typically made of a plastic material; and an electrolyte, which is a conductive organic solvent that saturates the other materials, thereby providing a mechanism for conducting ions between the negative and positive electrodes. These materials are typically packaged in cans (such as the prior art) Figure 1 As shown), wound together, or stacked together. There are many other configurations that can be used for such battery production purposes, including pouch cells, square cells, button cells, cylindrical cells, wound square cells, wound pouch cells, and the list goes on. These batteries, when properly made and handled with care, can provide energy for a variety of applications for thousands of charge and discharge cycles without any obvious safety incidents. However, as described above, certain events, especially certain defects, can cause internal short circuits between internal conductive materials, resulting in heating and internal thermal runaway, which is known to be the ultimate cause of fires in such lithium batteries. As described above, such events may also be caused by internal defects, including the presence of metal particles in the battery, burrs on the current collector material, fine points or holes in the separator (whether included during subsequent processing or caused during subsequent processing), misalignment of the battery layers (unwanted conductivity caused by leaving "openings"), external debris that penetrates into the battery (such as road debris that hits a moving vehicle), the battery itself is broken and / or unstable (for example, due to an accident), charging the battery in a confined space, etc. Generally speaking, these types of defects are known to result in the creation of a small electronic conduction path between the negative electrode and the positive electrode. When such an event occurs, if the battery is subsequently charged, such a conduction path may result in the discharge of the battery, through which excessive heat is ultimately generated, thereby damaging the battery structure and endangering the underlying devices powered thereby. Combined with the presence of a flammable organic solvent material as the battery electrolyte, which is often necessary for the battery to be operable, this excessive heat has been shown to cause it to ignite, ultimately creating a very dangerous situation. Such problems are difficult to control, at least once they begin, and have resulted in serious injuries to consumers. By providing a battery that delivers electrical energy without damaging the flammable organic electrolyte, this potentially catastrophic situation can certainly be avoided.
[0005] Excessive internal heat generation may further cause the plastic separator to shrink, causing it to move away from the battery, separate, or otherwise increase the short circuit area within the battery. In this case, the larger exposed short circuit area within the battery may cause continued current flow and increase heat therein, resulting in a high temperature event, which can cause significant damage to the battery, including rupture, ventilation, and even flames and fire. Such damage is particularly problematic because fire and worse consequences can occur quickly and may cause the battery and potentially the underlying device to explode, thereby also posing a significant risk to the user.
[0006] Lithium batteries (of various types) are particularly susceptible to problems related to short circuits. As described above, typical batteries tend to exhibit increased discharge rates when exposed to high temperatures, which can sometimes lead to uncontrolled (runaway) combustion and fire as described above. Due to these possibilities, certain regulations have come into effect to govern the actual use, storage, and even transportation of such battery items. Of course, the ability to implement appropriate protocols to prevent runaway events related to short circuits is very important. However, there remains the question of how to actually solve such problems, especially when parts production is provided from countless suppliers and many different locations around the world.
[0007] Some have honed in on attempts to provide appropriate and / or improved separators to help mitigate the potential for such lithium battery fires. Plastic films with low melting points and / or shrinkage appear to create a higher potential for such battery fire events. Thus, the general idea is to include certain coatings on such separator materials without reducing their electrolyte isolation capabilities during actual use. Thus, for example, ceramic particles have been used as coatings for polypropylene and / or polyethylene films as a means of improving the dimensional stability of such films (e.g., increasing the melting point). Binder polymers are also included as ingredients to improve cohesion between ceramic particles and adhesion to plastic films (films). However, in practice, the heat increase imparted to the entire film structure of the ceramic particle coating has been found to be relatively low, making the primary factor in such separator problems the actual separator material itself.
[0008] As a result, separator materials have been designed and implemented, at least in part, that are more thermally stable than the polyethylene and polypropylene porous membranes that form the base of such typical ceramic-coated separators. These low shrinkage, dimensionally stable separators exhibit shrinkage of less than 5% when exposed to temperatures of at least 200°C (up to 250°C, 300°C, and even higher), which is far superior to the high shrinkage exhibited by bare polymer films (greater than about 40% at 150°C) and the high shrinkage of ceramic-coated films (greater than 20% at 180°C) (comparisons of such shrinkage are provided in the prior art Figure 2Such low shrinkage materials may alter the thermal degradation mechanisms inside the target battery when a short circuit occurs. When a short circuit occurs in such a battery cell, heat will always be generated. If the separator does not shrink due to such a short circuit event, heat will continue to be generated and "accumulated" until another material within the battery degrades. This phenomenon has been simulated using industry standard nail penetration tests. For example, even with a separator that included para-aramid fibers and showed shrinkage stability up to 550°C, this test cell still showed a tendency to short circuit with unique internal results. After such treatment, such a battery was studied more closely, wherein the battery was opened, the excess electrolyte was evaporated, the battery was filled with epoxy resin, and then cut perpendicular to the nails, which were left in the battery. Scanning electron microscopy images were then taken using backscattered electron imaging (BEI), which is able to map different battery elements to show the effects of such nail penetration activity. These prior art Figure 3A and Figure 3B Shown in.
[0009] In the existing technology Figure 3A In the figure, it is noted that the copper layer is always closer to the nail than the aluminum layer. It should also be noted that the high stability separator remains intact between the electrodes. Figure 3B A higher magnification of the end of one aluminum layer is shown, showing it ending in a cracked gray matter layer. This was studied with BEI, and the results showed that the resulting substance is actually aluminum oxide, an insulating ceramic. This evidence led to the conclusion that when the separator itself is thermally stable, the aluminum current collector oxidizes, effectively breaking the circuit (as a result, any short circuits will stop once the insulating aluminum oxide is formed). Once the circuit is broken, the current will stop flowing and no heat will be generated, reversing the process, which would lead to thermal runaway if the stability of the separator was poor.
[0010] However, this possible solution is limited to simply replacing the diaphragm with higher shrinkage properties.
[0011] While such a simple solution appears to be valuable, there are still other manufacturing procedures and specific components (such as ceramic coated diaphragm types) that are already widely used and may be difficult to replace with recognized battery products. Therefore, despite the obvious benefits of utilizing and including thermally stable diaphragms, unwanted battery fires may still occur, especially when ceramic coated diaphragm products are considered safe for such purposes. Therefore, it has been determined that in addition to utilizing such highly thermally stable diaphragm materials, there is at least another separate internal battery cell structural mechanism that can remedy or at least reduce the chance of heat generation due to internal short circuits. In this case, the complete internal circuit is stopped due to the formation of a de facto internal fuse, and the occurrence of a short circuit within such a battery cell will not result in harmful high temperature damage. However, to date, no technology has been proposed in the lithium battery field that can easily solve these problems. The present invention provides such a very desirable method, making lithium battery cells extremely safe and reliable in multiple markets.
[0012] Therefore, there is a need for a novel and improved lithium energy storage device with an internal fuse that can be used to withstand certain defects in a target lithium battery by providing an internal fuse on the surface in the target lithium battery itself, thereby preventing undesirable high temperatures caused by short circuits. In this regard, the technology of the present invention substantially meets this need. In this regard, a lithium energy storage device with an internal fuse in accordance with the technology of the present invention substantially departs from the conventional concepts and designs of the prior art, and in doing so provides a device that is primarily developed to withstand certain defects in a target lithium battery, which prevents the battery from short circuiting by providing an internal fuse on the surface in the lithium battery of the present invention itself, thereby preventing the generation of undesirable high temperatures. Summary of the invention
[0013] In view of the aforementioned disadvantages inherent in the known types of lithium batteries in the prior art, the present invention provides an improved lithium energy storage device with an internal fuse and overcomes the above-mentioned disadvantages and weaknesses of the prior art. Thus, the overall purpose of the present invention technology (which will be described in more detail later) is to provide a new and improved lithium energy storage device and method with an internal fuse, which has all the advantages of the prior art mentioned so far and many novel features, thereby producing a lithium energy storage device with an internal fuse (whether used alone or in any combination thereof) that cannot be foreseen, discovered, suggested or implied by the prior art.
[0014] A significant advantage of the present disclosure is the ability to provide a mechanism for interrupting the conductive path when an internal short circuit occurs through a structural assembly, thereby stopping or greatly reducing the flow of current that may generate heat within the target battery cell. Another advantage is the ability to provide such a protective structural form within a lithium battery cell, which also provides beneficial weight and cost improvements for the manufacture, transportation and utilization of the entire battery. Therefore, another advantage is to generate and maintain an internal fuse structure within the target battery cell until it is necessary to activate it. Another advantage is to provide a lighter weight battery by utilizing a thin film-based current collector that prevents thermal runaway during a short circuit or similar event. Another advantage is the ability to utilize a flammable organic electrolyte material within the battery without any significant ignition tendency during a short circuit or similar event.
[0015] Thus, the present disclosure includes an energy storage device comprising: a negative electrode, a positive electrode, at least one polymer separator or fabric separator present between the negative electrode and the positive electrode, and at least one current collector in contact with at least one of the negative electrode and the positive electrode, the negative electrode or the positive electrode being inserted between at least a portion of the current collector and the separator, the current collector comprising a conductive material coated on the polymer material substrate, wherein the current collector stops conducting at the contact point when exposed to a short circuit at the operating voltage of the energy storage device, the voltage being at least 2.0 volts. An example is a current density of 0.1 amperes per square millimeter at the contact point, and a tip size of 1 square millimeter or less. Of course, for larger batteries, the required threshold current density may be higher, and the battery may only stop conducting at a current density of at least 0.3 amperes per square millimeter (such as at least 0.6 amperes per square millimeter, or even at least 1.0 amperes per square millimeter). The present disclosure also includes methods of utilizing such beneficial current collector components in energy storage devices (whether or not they are batteries, such as lithium-ion batteries, capacitors, etc.).
[0016] Additionally, a greater current density may be carried in a very short time or in a very small, sharp probe. In this case, a larger current (e.g., 5 amps, 10 amps, or even 15 amps) may be sustained for a very short period of time (e.g., less than 1 second, or less than 0.1 second, or even less than 1 millisecond (0.001 second)). Within the present disclosure, while it is possible to measure larger currents, the delivery time for such currents is short enough that the total energy delivered is very small and insufficient to generate enough heat to cause a thermal runaway event within the target battery. For example, a short circuit within a conventional architecture battery is known to produce a 10 amp current for 30 seconds at 4.2 volts, resulting in 1200 joules of energy being delivered to a small, localized area within such a battery. Such a measurement could result in a temperature increase of approximately 300°C in a 1 gram portion of the target battery, a temperature high enough to not only melt conventional separator materials present therein, but also place the entire battery in a runaway thermal state (which, as noted above, could result in the aforementioned damage to the electrolyte materials present therein, and could potentially damage not only the target battery, but also the devices / apparatus upon which it is dependent, as well as the surrounding environment). Thus, it is certainly possible that the ability to reduce the duration of short circuits and the resulting levels of transferred energy associated with low joule measured short circuits, thermal runaway (and the potential disasters associated therewith) could be circumvented (if not avoided entirely). For example, reducing the short circuit residence time within the current collector to 1 millisecond or less could subsequently reduce the transferred energy to 0.04 joules (as opposed to the 1200 joules noted above, e.g., resulting in an excessive 300 degrees Celsius or more within a 1 gram localized area of the target battery). Thus, such a low level would only result in a temperature increase of 0.01°C within the 1 gram localized area of the battery, thereby preventing thermal runaway within the target battery as well as within the entire battery.
[0017] Therefore, another significant advantage of the present disclosure is to provide a battery current collector that greatly limits the transmission time of the current level applied to the target current collector surface by the probe tip (so as to controllably simulate the effects of internal manufacturing defects, dendrites, or external events that cause internal short circuits in the target battery) to less than 1 second, preferably less than 0.01 seconds, more preferably less than 1 millisecond, and most preferably even less than 100 microseconds (especially for larger currents). Of course, such current will be limited by the internal voltage of the battery, which may be 5.0V, 4.5V, 4.2V or lower, such as 4.0V or 3.8V, but the minimum value is 2.0V.
[0018] This novel current collector assembly is actually contrary to those commonly used and found in lithium (and other types of) batteries and energy storage devices today. The standard current collector provided is a conductive metal structure, such as an aluminum and / or copper panel, whose thickness is believed to provide some type of protection for the entire battery structure. These typical current collector structures are designed to provide the maximum possible conductivity within weight and space constraints. However, it seems that this idea has actually been misunderstood, especially because the thick panels commonly used in energy storage devices today can actually not only arc when a short circuit occurs, but also greatly exacerbate temperature runaway when this occurs. For example, such a short circuit may be caused by dendrite formation within the separator. This deformity (whether caused in or during manufacturing, or caused by long-term use and potential drop) may allow voltage to be accidentally transferred from the negative electrode to the positive electrode, resulting in increased current and temperature increase at the location where it occurs. In fact, one possible source of short circuits that cause defects is burrs (common today) formed on the edges of thick typical current collectors when cut or cut with worn blades during repeated manufacturing processes of multiple products. However, it has been repeatedly analyzed and understood that standard current collector materials only show a tendency to spark and allow temperature rise, and further allow the current present in this case to continue to pass through the device, thereby allowing unconstrained generation and movement, without any way to reduce the increase in current and temperature levels. This problem directly leads to uncontrolled high temperature results; if there is no internal mechanism to stop this situation, it is usually very likely to cause a fire and eventually burn the device. In addition, the current path (charging direction) of the standard current collector remains quite static before and during the short circuit event, basically showing the potential movement of the same charge expected from the positive electrode to the negative electrode and then moving horizontally along the current collector in a specific direction. However, in the event of a short circuit, this current path cannot prevent or at least reduce or delay this charge movement, in other words, allowing rapid discharge in an uncontrolled manner throughout the battery itself. Coupled with the high temperature associated with this rapid discharge, it can lead to the above-mentioned catastrophic problems (fire, explosion, etc.).
[0019] On the contrary, again, it is highly unexpected and contrary to the typical structure and configuration of lithium batteries, at least the current collector using the present invention results in extremely high current density measurements (due to the reduced thickness of the conductive element) and prevents charge movement (e.g., no charge direction) in the event of a short circuit. In other words, in the case where the current collector assembly disclosed in the present invention meets specific structural constraints, the current density is increased to such an extent that the resistance level produces extremely high but controllable high temperature relative to the short circuit. Therefore, this resistance level causes the conductive material (e.g., aluminum and / or copper as an example only) to receive the short circuit charge, but due to the structural form provided by the present invention, the conductive material will immediately react to this high temperature local charge. Combined with the other structures of this current collector assembly, that is, the actual lack of dimensionally stable polymeric material in contact with this conductive material layer, the conductive material is immediately oxidized at the charging point thereon, leaving, for example, aluminum or copper oxide (both non-conductive materials). Through the generation of this instantaneous non-conductive material, the short circuit charge appears to dissipate due to the lack of direction available for its movement. Thus, with the current collector now described, the occurrence of an internal short circuit results in an immediate cessation of current flow, thereby effectively utilizing the immediate high temperature caused by such a short circuit to create a barrier that impedes further charge movement. In this way, the lack of further current flow (of course associated with the short circuit) throughout the body of the energy storage device reduces this undesirable event to the point where the short circuit is completely suppressed, no runaway current or high temperature results thereafter, and, perhaps most importantly, the current collector remains viable for its original protective purpose because the subsequent presence of the local non-conductive material does not result in any appreciable reduction in current flow when the energy storage device (battery, etc.) is operating as intended. In addition, the relatively small area produced by the non-conductive material leaves a large surface area on the current collector, etc., for further use without the need for repair, replacement or other remedial measures. The need to ensure this situation will of course not always occur, but as now disclosed, the possibility of such high temperature damage and destruction events in the absence of certain preventive and corrective measures is actually still far higher than generally accepted. As a result, the entire current collector becomes a two-dimensional electrical fuse due to its instability under short-circuit conditions, thereby preventing the potentially catastrophic high current associated with short circuits by exploiting the transient effect of large currents to destroy the current collector's ability to conduct current at the short-circuit point.
[0020] These advantages associated with this novel resulting current collector that can be set allow similar end results to be achieved through many different alternatives. In any of these alternative configurations, this current collector as described in the present invention acts as an internal fuse within the target energy storage device (e.g., lithium battery, capacitor, etc.) on the surface. However, in each case (alternative), there is a current collector including a polymer layer that is metallized on one or both sides thereof, and at least one metallized side is in contact with the negative or positive electrode of the target energy storage device. Then, an alternative is that the total thickness of the entire metallized (coated) polymer substrate of the current collector is less than 20 microns, and the resistance measurement is less than 1 ohm / □. Typical current collectors can show these features, but the weight is much higher than that of current collectors made with reinforced polymer substrates, and there is no inherent safety advantage disclosed in the present invention. However, in this alternative structure, a very thin component allows a short circuit that reacts with the metal coating and is related to the total resistance level to produce a localized area of metal oxide through the excessive temperature caused by the current spike during this short circuit, which can immediately prevent the current from flowing further thereon.
[0021] Another possible alternative to this novel current collector is to provide a temperature-dependent metal (or metallization) material that shrinks from a heat source during a short circuit, or easily degrades into a non-conductive material (such as, as an example, aluminum oxide from an aluminum current collector) at a specific material location (as mentioned above in a different manner). In this way, the current collector becomes thermally weak, in sharp contrast to the aluminum and copper current collectors used today, which are quite thermally stable to high temperatures. As a result, alloys of metals with lower intrinsic melting temperatures can be degraded at lower short-circuit current densities, thereby improving the safe production of current collectors by coating a conductive material (such as copper or aluminum) layer on a fiber or film that exhibits a higher shrinkage rate at a lower temperature. Another possible way to achieve this result is to make a current collector by coating a conductive material (such as copper or aluminum as described above) layer on a fiber or film, which swells or dissolves in the electrolyte when the material is heated to a temperature that is higher than the operating temperature of the battery but lower than the temperature that may cause thermal runaway. Examples of such polymers that can swell in lithium-ion electrolytes include polyvinylidene fluoride and polyacrylonitrile, but there are other polymers well known to those skilled in the art. Another way to accomplish this alternative internal electrical fuse generation process is to coat the substrate with a metal (e.g., aluminum) that can be oxidized under heating, with a total metal thickness much lower than the total metal thickness typically used for lithium batteries. For example, the very thin aluminum current collectors used today can be 20 microns thick. A total coating thickness of less than 5 microns will interrupt the circuit faster, while a coating thickness of less than 2 microns or even less than 1 micron will interrupt the circuit even faster. Another way to achieve conductive path interruption is to provide a current collector with limited conductivity that will degrade at high current densities around the short circuit, similar to the degradation found in commercial fuses today. This can be achieved by providing the current collector with a resistivity greater than 5 milliohms / □ or 10 milliohms / □, or perhaps preferably greater than 20 milliohms / □, or greater than 50 milliohms / □, which may be more preferably. For cells designed for high power, a relatively low resistance may be used compared to cells designed for lower power and higher energy, and / or a relatively high resistance may be used, and current collectors of different resistivity may be selected differently. Yet another way to achieve interruption of the conductive path is to provide a current collector that oxidizes to a non-conductive material at a temperature much lower than aluminum, thereby rendering the current collector inert in the region of the short circuit before the separator degrades. Certain aluminum alloys oxidize faster than aluminum itself, and these alloys can cause the conductive path to degrade faster or at lower temperatures.As a possible alternative, any type of metal having such thin layer capacity and exhibiting conductivity may be used, including but not limited to: gold, silver, vanadium, rubidium, iridium, indium, platinum, etc. (basically, by using very thin layers, the costs associated with the use of such metals can be greatly reduced without sacrificing conductivity, and still allowing protection from thermal runaway potentials during short circuits or similar events). Similarly, different metal layers may be used, or even discrete areas of metal deposited in or as a separation layer component may be utilized. Of course, one side of such a coated current collector substrate may also include a different metal variety than the opposite side, and may also have different layer thicknesses in comparison.
[0022] A way to improve the electrical performance of the battery would be to ensure that the current collector of the coating includes two conductive coating sides, so that the coating from one side to the other side is allowed to have conductivity on the surface. For example, for uncoated polymer films, such a result is impossible. However, it has been recognized that, as a non-limiting example, such double-sided electrical conductance (conductivity throughput) can be achieved by including a certain percentage of conductive fibers, or non-woven fabrics loaded with conductive materials, or non-woven fabrics made of conductive materials (such as carbon fibers or metal fibers), or non-woven fabrics containing fibers coated with conductive materials (such as fibers with metal coatings on the surface) as described above. Another type of novel thin current collector material with conductivity from top to bottom can be, for example, by utilizing inherent conductive materials (such as conductive polymers, such as polyacetylene, polyaniline or polyvinyl pyrrolidine) or via a conductive material (such as graphite or graphene or metal particles or fibers) in or after the film manufacturing process. In addition, another possible double-sided thin current collector material is a polymer substrate with small perforations and metal (aluminum or copper) coated on its side during metallization. This conductivity from one side to the other would not require anything like a conductive coating to conduct electricity.
[0023] Thus, such alternative configurations that ostensibly achieve the same current collector results and physical properties include: a) wherein the total thickness of the coated polymer substrate is less than 20 microns and the resistance is less than 1 ohm / □; b) the current collector comprises a conductive material coated on a substrate comprising a polymer material, wherein the polymer material exhibits a thermal shrinkage of at least 5% at 225°C; c) wherein the metallized polymer material of the current collector swells in the electrolyte of the battery, and this swelling increases as the polymer material is heated; d) wherein the total thickness of the current collector conductive material when applied to the polymer substrate is less than 5 microns; e) wherein the conductivity of the current collector is 10 milliohms / □ to 1 ohm / □; and f) wherein the metallized polymer substrate of the current collector exhibits a porosity of up to 60%. Utilizing any of these alternative configurations in an energy storage device having a separator that exhibits a thermal shrinkage of less than 5% after 1 hour at 225°C will also be within the scope of the present disclosure. The overall utilization (method of use) of this type of energy storage device (battery, capacitor, etc.) is also included herein.
[0024] Although the main advantage of the present invention is to enhance the safety of the battery, there are other advantages as described above, including reducing the weight of the entire energy storage device by reducing the metal weight associated with such a current collector assembly. Again, it is completely contrary to use a thin metallized coated (especially low dimensional stability) polymer layer for the current collector in such a battery product. The current habit of the industry is still this idea: a larger amount of actual metal and / or insulator components are required to achieve the required protection effect (especially from potential short circuit events). It has now been unexpectedly realized that this paradigm is not only incorrect, but the effective remedy for the problem of internal short circuits in lithium batteries, etc., is to reduce rather than increase the amount of metal and couple it with a thermally unstable base layer. Therefore, it is again very unexpectedly realized that a thin metal layer with such an unstable base layer provides the ability to resist and effectively prevent discharge events during short circuits, and the overall effect is not only a safer and more reliable result, but also a greatly reduced overall weight and volume of such components. Therefore, the unexpected benefits of improved properties with reduced weight and volume requirements in energy storage products (batteries, etc.) are more in line with the industry than initially understood.
[0025] As further explanation, the density is 2.7 g / cm 3 The weight of 20 micron thick aluminum is 54g / m 2 However, in a 10 μm thick polypropylene film (density 0.9 g / cm 3 ) with a coating of 1 micron of the same metal weighs 11.7 g / m 2 Such a weight reduction of the current collector can reduce the weight of the entire target energy storage device (e.g., a battery), thereby increasing mobility, increasing fuel mileage or electric range, and generally improving the value of mobile electric applications.
[0026] In addition, due to the high strength of the film, the above examples can also be made thinner, for example, a total thickness of 11 microns compared to 20 microns again reduces the volume of the battery, thereby effectively increasing the energy density. In this way, a current collector with a total thickness of less than 15 microns, preferably less than 12 microns, more preferably less than 10 microns, and most preferably less than 8 microns can be manufactured and used for this purpose and function.
[0027] Since the volume resistivity of aluminum is 2.7×10 -8 Ohm·meter, the volume resistivity of copper is 1.68×10 -8 Ohm·meter, thin coatings can be made less than 1 ohm / □ or less than 0.5 ohm / □, or even less than 0.1 ohm / □ or less than 0.05 ohm / □. The thickness of these conductive coatings can be less than 5 microns, preferably less than 3 microns, more preferably less than 2 microns, and perhaps most preferably even less than 1 micron. It is very contradictory that suitable performance can be obtained by using much less metal when standard materials commonly used in the market contain 10 microns or more of metal. In fact, most of the metals present in typical storage devices are included to provide suitable mechanical properties for high-speed and automated processing. One of the advantages of the present invention is the use of a much lower density polymer material to provide mechanical properties, thereby reducing the metal thickness to a level that improves battery safety because the current collector cannot carry the highly dangerous current density caused by internal electrical shorts and leading to thermal runaway, smoke and fire.
[0028] In addition, these conductive layers can be made of multiple layers. For example, the aluminum layer can be a base layer coated with a thin layer of copper. In this way, the bulk conductivity can be provided by aluminum, which is lightweight, cheap, and can be easily deposited by vapor deposition techniques. Copper can provide additional conductivity and passivation for the negative electrode without adding significant additional cost and weight. This example is given only for illustration, and those skilled in the art can provide many other multi-layer conductive structures, any of which are excellent examples of the present invention.
[0029] These thin metal coatings will generally result in higher resistances than those in aluminum or copper current collectors of conventional practice, thereby providing a significant feature of the present invention in comparison. Such novel suitable current collectors can be made greater than 10 milliohms / □, preferably greater than 20 milliohms / □, more preferably greater than 50 milliohms / □, and perhaps most preferably even greater than 100 milliohms / □.
[0030] In addition, batteries made with the above-mentioned thermally weak current collectors can become safer if the separator has high thermal stability, such as low shrinkage at high temperatures, including less than 5% shrinkage after exposure to a temperature of 200°C for one hour, after exposure to 250°C for one hour, and more preferably after exposure to a temperature of 300°C for one hour. Existing separators are made of polyethylene with a melting temperature of 138°C and polypropylene with a melting temperature of 164°C. Figure 2 As shown, these materials show a shrinkage of greater than 50% at 150°C; such a result is too high for use with thin current collectors as described in the present invention. To remedy this problem, it has been recognized that it is necessary to use certain separators that shrink less than 50%, even less than 30% or less than 10% at 150°C as measured in accordance with Section 3.5 of NASATM-201O-216099. Even ceramic-coated separators show significant shrinkage at relatively moderate temperatures, breaking completely or shrinking more than 20% at 180°C. Therefore, it is desirable to use a separator that does not break under exposure conditions of 180°C (at least) when measured according to the same test standard and shrinks no more than 20%, more preferably no more than 10%. The most preferred embodiment is to use a separator that shrinks less than 10% when exposed to temperatures of 200°C, 250°C or even 300°C.
[0031] For any of these metallized substrates, it is desirable to have a low thickness to facilitate increasing the energy density of the battery. This thickness can be obtained by using any means, including calendering, compression, hot pressing, and even ablating the material on the surface in a manner that reduces the total thickness. These thinning processes can be performed before or after metallization. Therefore, it is desirable to have a total thickness of a metallized substrate less than 25 microns, preferably less than 20 microns, more preferably less than 16 microns, and most preferably less than 14 microns. It has been achieved that commercial polyester films have a thickness of up to 3 microns or even less than 1.2 microns. These types can be used as suitable substrates, and allow the total thickness of the current collector to be less than 10 microns, preferably less than 6 microns, and more preferably less than 4 microns. Such ultrathin current collectors (with suitable conductivity as described above and throughout the text) can allow higher energy density and have improved safety performance, which is a result that has not been explored so far.
[0032] It is also desirable for these metallized substrates to be lightweight. This can be achieved by using low density polymer materials such as polyolefins or other low density polymers including polyethylene, polypropylene and polymethylpentene, as examples only. It can also be achieved by having an open cell structure in the substrate or even by utilizing a low basis weight substrate. Thus, the density of the polymer used in the substrate can be less than 1.4 g / cm 3 , preferably less than 1.2 g / cm 3, and may be more preferably less than 1.0 g / cm 3 Moreover, the surface density of the substrate material can be less than 20g / m 2 , preferably less than 16g / m 2 , and may most preferably be less than 14 g / m 2 In addition, the surface density of the metal-coated polymer substrate material can be less than 40 g / m 2 , preferably less than 30g / m 2 , more preferably less than 25g / m 2 , and may most preferably be less than 20 g / m 2 .
[0033] Porous polymer substrates can also achieve low weight. However, the porosity cannot be too high for these materials because this would result in low strength and large thickness, which would not actually achieve the purpose of the objectives involved. Therefore, the porosity of such substrates will be less than about 60%, preferably less than 50%, and perhaps more preferably less than 40%. Since solid materials can be used for this type of metal-coated current collector, there is no lower limit to the porosity.
[0034] High strength is required to process the material into batteries at high speeds. This can be achieved by using elongated polymers (either from elongated fibers, or from uniaxially or biaxially elongated films).
[0035] As shown in the following description of the accompanying drawings, an energy storage device (whether a battery, capacitor, supercapacitor, etc.) is manufactured and provided according to the present invention, wherein at least one current collector exhibits no obvious current movement related characteristics after short circuiting in contact with the positive electrode and the negative electrode, or two separate current collectors in contact with the positive electrode and the negative electrode, and the diaphragm and electrolyte are stored and sealed in a standard (suitable) energy storage device container. In most cases, the positive electrode, negative electrode, container, electrolyte, and in some cases the diaphragm assembly are standard components. However, as disclosed herein, the current collectors utilized herein and in this article are not only novel and unexplored in the art, but also contradictory as actual energy storage device components. This is again described in more detail below.
[0036] As described above, in order to reduce (if not completely prevent) the chance of thermal runaway within a battery cell (particularly of the lithium-ion rechargeable type, but certainly other types as well), a means is needed to cause any short circuits therein to exist for a substantial period of time, reduce the residence time in or on the current collector, and ultimately exhibit a final energy level of minimal Joules (i.e., less than 10, preferably less than 1, and most preferably less than 0.01). Then, in this case, and as previously described, there is an electrical path from the negative electrode to the positive electrode and through the separator (with the thin conductive current collector in place) and the organic combustible electrolyte, it has been found that a low weight thin current collector allows such desirable results, particularly with respect to the dissipation of rogue charges on the current collector surface and without significant temperature increases that would cause the electrolyte components to ignite. Surprisingly and without being bound by any particular scientific explanation or theory, it is believed that the conductive nature of the thin current collector material allows the short circuit charge to reach only the thin conductive current collector and immediately produce a short duration high energy event that reacts between the metal on the current collector surface and the charge itself, thereby forming a metal oxide at that particular point on the current collector surface. The metal oxide provides insulation for further electrical activity, and the applied current dissipates instantaneously, leaving potential deformation within the current collector itself, but the metal oxide is present to prevent any further charge activity at that particular location. Therefore, the remaining current collector is intact and can provide the same capabilities as before, thereby further providing such protection for any more potential short circuits or similar phenomena. As an example, in the case of thermal runaway in a battery product of the prior art, the negative electrode, positive electrode, current collector and separator include an electrical path that generates heat and provides a spark to ignite the battery associated with the short circuit. Therefore, there is further an effective danger that the ion-transmitting flammable electrolyte allows for high temperature results associated with such unexpected charges. In essence, the heat generated at the current collector of the prior art causes an initial electrochemical reaction within the electrolyte material, which ultimately leads to the runaway ignition of the electrolyte material itself. Therefore, the inventive current collector disclosed in the present invention is particularly valuable when used in a battery cell including such a flammable electrolyte. For example, such an electrolyte typically includes an organic solvent, such as a carbonate, including propylene carbonate, ethylene carbonate, ethyl methyl carbonate, diethyl carbonate and dimethyl carbonate, etc. These electrolytes are usually present in the form of a mixture of the above materials and may be present with other solvent materials (including various types of additives). These electrolytes also have a lithium salt component, an example of which is lithium hexafluorophosphate LiPF6. Such electrolytes are preferred in the battery industry, but as mentioned above, they can indeed lead to dangerous situations. Again, this inventive current collector associated with other battery components significantly and surprisingly remedies these problems.
[0037] One way this current collector will exert its effectiveness is in the following test. A current source with voltage and current limits can be set to a voltage limit similar to the operating voltage of the energy storage device in question. The current can then be adjusted and the current collector tested in two configurations. First, a short strip of the current collector of known width is contacted by two metal connectors that touch the entire width of the sample. The current limit of the current source can be increased to see if there is a limit to the material's ability to carry current, which can be measured as the total current divided by the width, giving a result in A / cm, designated as the horizontal current density in this invention. The second configuration is to contact the ground of the current source to one of the full-width metal contacts, and then touch the tip of the probe (about 0.25mm) to the location along the current collector strip. 2 ). If the current is too high, it will burn out the local area and no current will flow. If the current is not too high for the current collector, the full current up to the current source limit will flow. The result is in A / mm 2 The current limit in units of , which is referred to herein as the vertical current density. In this way, a current collector capable of high current in both configurations would be similar to the prior art, and a current collector that can carry horizontal current when in full width contact but cannot carry similar vertical current under point contact would be an example of the invention described herein.
[0038] For example, it is desirable that the current collector can carry a horizontal current density of 0.1 A / cm or 0.5 A / cm, or 1 A / cm or 2 A / cm, or even 5 A / cm. For a current collector that can carry the above horizontal current densities, it is desirable that there is no current collector that can carry a current density of 0.1 A / cm. 2 or 0.5A / mm 2 or 1A / mm 2 or 2A / mm 2 Even 5A / mm 2 The vertical current density.
[0039] Such lithium-ion battery films may require certain unique processing steps due to their unique qualities. However, many processing steps well known in the art may also be used. In general, a method of manufacturing a lithium-ion battery having an inventive film includes the following steps:
[0040] a. Providing an electrode having at least one metallized substrate having a coating of an ion storage material;
[0041] b. Providing a counter electrode;
[0042] c. stacking the electrode and the counter electrode relative to each other, and inserting a diaphragm assembly between the electrode and the counter electrode;
[0043] d. providing a packaging material comprising an electrical contact component, wherein the contact comprises a portion present inside the packaging material and a portion present outside the packaging material;
[0044] e. electrically connecting the electrical contact to the metallized substrate;
[0045] f. introducing at least one liquid electrolyte with ions into the interior of the packaging material; and
[0046] g. Sealing the packaging material.
[0047] The metallized substrate may be any substrate as described in this disclosure.
[0048] As is known in the art, the ion storage material may be, for example, a positive electrode or negative electrode material of a lithium ion battery. The positive electrode material may include lithium cobalt oxide LiCoO2, lithium iron phosphate LiFePO4, lithium manganese oxide LiMn2O4, lithium nickel manganese cobalt oxide LiNi x Mn y Co z O2, LiNi x CO y Al z O2, or a mixture thereof, or other substances known in the art. The negative electrode material may include graphite, lithium titanate Li4Ti5O 12 , hard carbon, tin, silicon or mixtures thereof, or other materials known in the art. In addition, the ion storage materials may include those used in other energy storage devices such as supercapacitors. In such supercapacitors, the ion storage materials will include: activated carbon, activated carbon fibers, carbide-derived carbon, carbon aerogels, graphite, graphene, graphene, and carbon nanotubes.
[0049] The coating process can be any coating process generally known in the art. Knife-over-roll and slot die are commonly used coating processes for lithium-ion batteries, but other processes (including chemical plating) can also be used. In the coating process, the ion storage material is usually mixed with other materials, including a binder such as polyvinylidene fluoride or carboxymethyl cellulose, or other film-forming polymers. Other additives to the mixture include carbon black and other conductive additives.
[0050] The counter electrode includes other electrode materials having an electrochemical potential different from that of the ion storage material. Typically, if the ion storage material is a lithium ion negative electrode material, the counter electrode will be made of a lithium ion positive electrode material. In the case where the ion storage material is a lithium ion positive electrode material, the counter electrode can be a lithium ion negative electrode material. In the case where the ion storage material is a supercapacitor material, the counter electrode can be made of a supercapacitor material, or in some cases can be made of a lithium ion negative electrode or a lithium ion positive electrode material. In various cases, the counter electrode will include an ion storage material coated on a current collector material, which can be a metal foil or a metallized film as in the present invention.
[0051] In the lamination process, the inventive electrode is laminated with the counter electrode so that the electrode materials face each other and there is a porous separator between them. As is generally known in the art, the electrodes can be coated on both sides and the electrode stack formed by the inventive electrode and the counter electrode is alternated with a separator between each layer. Alternatively, as is also known in the art, strips of electrode material can be stacked as described above and then wound into a cylinder.
[0052] The packaging material may include a rigid package such as a can for a cylindrical battery, a flat rigid housing, or a polymer bag. In each case, there must be two mechanisms for making electrical contact through the housing that are capable of maintaining different voltages and capable of conducting current. In some cases, one portion of the housing itself forms a mechanism, while another portion is a distinct portion of the housing that is electrically isolated from the first portion. In other cases, the housing may be non-conductive but allow two metal conductors to protrude through the housing, commonly referred to as tabs.
[0053] Connecting the mechanism to make electrical contact with the metallized substrate can include conventional methods such as welding, encapsulation, clamping, stapling, riveting or other mechanical means. Because the metal of the metallized substrate can be very thin, in order to achieve an interface that allows large currents to flow, face-to-face contact is usually required, thereby creating a large surface area between the mechanism for electrical contact through the housing and the metallized substrate. In order to carry sufficient current, the surface area should be greater than 1 square millimeter (10-12 square meters), but may need to be greater than 3 square millimeters, even 5 square millimeters, or more preferably 10 square millimeters.
[0054] The liquid electrolyte is typically a combination / mixture of a polar solvent and a lithium salt. As mentioned above, commonly used polar solvents include propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, but other polar solvents may be used, including ionic liquids or even water. Commonly used lithium salts in the industry include, but are not limited to: LiPF6, LiPF4, LiBF4, LiClO4, etc. The electrolyte may also contain additives known in the art. In many cases, the electrolyte may be flammable, wherein the safety features of the inventive metallized substrate current collector can advantageously prevent dangerous thermal runaway events that lead to ignition and damage to the battery and the exterior of the battery.
[0055] One aspect of the present technology can be an energy storage device comprising: a negative electrode, a positive electrode, at least one separator present between the negative electrode and the positive electrode, at least one liquid electrolyte, and at least one current collector in contact with at least one of the negative electrode and the positive electrode. The current collector may include a top surface and a bottom surface. The separator may be a polymer structure, a ceramic structure, or a non-woven fabric structure. The current collector may be a non-conductive material having a conductive coating on both surfaces thereof. The current collector may exhibit the ability to carry an effective current density when operating normally along a current path horizontally along the current collector. When subjected to the shrinkage test described in Section 3.5 of NASATM-2010-216099, the polymer separator or fabric separator does not break or shrink by no more than 20% at 180°C.
[0056] Another aspect of the present technology is an energy storage device comprising: a negative electrode, a positive electrode, at least one separator present between the negative electrode and the positive electrode, at least one liquid electrolyte, and at least one current collector in contact with at least one of the negative electrode and the positive electrode. The current collector may include a top surface and a bottom surface. The separator may be a polymer structure, a ceramic structure, or a non-woven fabric structure. The current collector may be a non-conductive material substrate having a conductive coating on both surfaces thereof. The current collector may exhibit the ability to carry an effective current density when operating normally along a current path horizontally along the current collector. The non-conductive material substrate may have conductivity from a conductive material coated on one side to a conductive material coated on the other side.
[0057] Another aspect of the present technology is a method for manufacturing an energy storage device, which includes the following steps: providing an electrode having at least one metallized substrate coated with an ion storage material; providing a counter electrode; stacking the electrode and the counter electrode relative to each other and inserting a diaphragm assembly between the electrode and the counter electrode; providing a packaging material including an electrical contact assembly, wherein the contact includes a portion present inside the packaging material and a portion present outside the packaging material; electrically connecting the electrical contact to the metallized substrate; introducing at least one liquid electrolyte with ions into the interior of the packaging material; and sealing the packaging material.
[0058] These and other objects of the present invention and the various novel features which characterize the present invention are particularly pointed out in the appended claims and form a part of this disclosure. For a better understanding of the present invention, its operating advantages and specific objects achieved by its use, reference should be made to the accompanying drawings and descriptive contents, in which embodiments of the present invention are shown. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] The present invention will be better understood and other objects besides the above mentioned objects will become apparent when considering the following detailed description of the present invention. Such description refers to the accompanying drawings, in which:
[0060] Figure 1 It is a prior art illustration of the structure of a wound battery (such as a 18650 battery).
[0061] Figure 2 Prior art illustration of shrinkage as a function of temperature measured by dynamic mechanical analysis of several lithium ion battery separators as measured in accordance with NASA / TM-2010-216099 "Battery Separator Characterization and Evaluation Procedures for NASA's Advanced Lithium Ion Batteries", Section 3.5, which is incorporated herein by reference. Included are first generation separators (Celgard PP, Celgard tri-layer), second generation separators (ceramic PE), and third generation separators (silver, gold, silver AR).
[0062] Figure 3A is a prior art illustration of a scanning electron micrograph (SEM) of a cross section of a pouch cell that has been subjected to a nail penetration test. The layers are aluminum and copper mapped by BEI (backscattered electron imaging). The nail is vertical on the left. In each case, the aluminum layer has been retracted from the nail, leaving behind a "skin" of aluminum oxide, the insulator.
[0063] Figure 3B yes Figure 3A A magnified prior art illustration of one layer of the image shown. It shows a close-up of the aluminum oxide layer and also reveals that the separator has not shrunk at all and still separates the electrodes to the very edges.
[0064] Figure 4 is an illustration of the invention where the thin layer of conductive material is on the outside and the central substrate is a layer that is thermally unstable at the temperature required for thermal runaway. The substrate can be a melting layer, shrinking layer, dissolving layer, oxidizing layer or other layer that undergoes thermal instability at temperatures between 100°C and 500°C.
[0065] Figure 5A is a prior art illustration of thick aluminum current collectors, typically between 12 and 20 microns.
[0066] Figure 5B is an illustration of the invention showing a 14 micron thick substrate with 1 micron of aluminum on each side. In the case of the inventive current collector, it cannot carry the high currents associated with short circuits, as thick current technology can.
[0067] Fig. 6A and Figure 6B The images of Comparative Examples 1-2 respectively after being touched by the tip of a hot soldering iron are shown. The Comparative Example showed no change after being touched by the hot soldering iron.
[0068] Figure 7A-7C Images of Examples 1-3 after being touched by the tip of a hot soldering iron are shown.
[0069] Examples 1-3 all exhibit shrinkage as described in this disclosure for substrates to be metallized.
[0070] Figure 8A-8C Images of Examples 4-6, respectively, after being touched by the tip of a hot soldering iron are shown. Example 4 exhibits shrinkage as described in the present disclosure for substrates to be metallized. Example 5 has fibers that dissolve in a lithium ion electrolyte under heating. Example 6 is an example of a thermally stable substrate that requires a thin conductive layer to function as the present invention does.
[0071] Fig. 9 A SEM at twice the magnification of a cross section and one showing the metallized surface of one possible embodiment of a current collector described in Example 9. The metal is clearly much thinner than the original 20 micron thick substrate.
[0072] Fig. 10A and Fig. 10B is an optical micrograph of Comparative Examples 3 and 4 after shorting, showing ablation of the area around the short but without the hole.
[0073] Fig.11A and Fig. 11B are optical micrographs of two areas of Example 14 after short circuiting, showing clear holes in the material caused by the high current density of the short circuit.
[0074] Fig.12 A diagram showing the size and shape of the current collectors used in the embodiments described below. DETAILED DESCRIPTION
[0075] The following description and examples are merely representative of potential implementations of the present disclosure. One of ordinary skill in the art will well appreciate the scope of the present disclosure and its scope in the following appended claims.
[0076] As described above, the present invention is a major shift and goes against all previous understandings and remedies performed within the lithium battery (and other energy storage device) industry. Instead, the novel devices described herein provide many beneficial results and properties that have heretofore been unexplored (let alone unexpected) in this area. Initially, though, as a comparison, it is important to note the clear differences involved between existing devices and the devices currently disclosed and broadly encompassed by the present invention.
[0077] Short Circuit Event Example
[0078] Comparative Example 1
[0079] The positive electrode of the lithium iron phosphate battery was obtained from GB Systems in China. The aluminum tab was removed as an example of a commercial current collector, and the thickness, surface density, and resistance were measured, which are shown in Table 1 below. The aluminum foil was then touched to a hot soldering iron for 5 seconds, and the temperature was measured using an infrared thermometer to be 500°F to 525°F. There was no effect of the soldering iron touching the current collector. The thickness, surface density, and resistance were measured. The material was placed in an oven at 175°C for 30 minutes, and the shrinkage was measured. Photos were taken, such as Fig. 6A shown. Figure 5A The performance of conventional current collectors within such a comparative cell is provided.
[0080] Comparative Example 2
[0081] The negative electrode of the lithium iron phosphate battery was obtained from GB Systems in China. The copper tab was removed as an example of a commercial current collector, and the thickness, surface density, and resistance were measured, which are shown in Table 1 below. Then, the copper foil was touched with a hot soldering iron in the same manner as in Example 1. There was no effect of the soldering iron touching the current collector. The thickness, surface density, and resistance were measured. The material was placed in an oven at 175°C for 30 minutes, and the shrinkage was measured. Photos were taken, such as Fig. 6A As shown in Comparative Example 1, Figure 5A A representation of the internal structure of such a battery is provided. The thickness of the current collector is important because it is a monolithic metal structure, not the thin type currently disclosed.
[0082] Example 1
[0083] Polypropylene lithium battery separator material was obtained from MTI. The material is manufactured by Celgard and is product number 2500. The thickness, surface density and resistance were measured and are shown in Table 1 below. Then, in the same manner as in Example 1, a hot soldering iron was touched to the separator. A thermometer was touched to the current collector to create a small hole. The diameter was measured and included in Table 1. The thickness, surface density and resistance were measured. The material was placed in an oven at 175°C for 30 minutes and the shrinkage was measured. Photos were taken, such as Fig. 7A shown.
[0084] Example 2
[0085] The ceramic-coated polyethylene lithium battery separator material was obtained from MTI Corporation. The thickness, areal density, and resistance were measured, which are shown in the following Table 1. Then, in the same manner as in Example 1, the separator was touched with a hot soldering iron.
[0086] The current collector was touched with a soldering iron to create a small hole. The diameter was measured and included in Table 1. The thickness, areal density and resistance were measured. The material was placed in an oven at 175°C for 30 minutes and the shrinkage was measured. Photos were taken, such as Fig. 7A shown.
[0087] Example 3
[0088] The ceramic coated polypropylene lithium battery separator material was obtained from MTI. The thickness, areal density and resistance were measured and are shown in Table 1 below. The separator was then touched with a hot soldering iron in the same manner as in Example 1. The current collector was touched with a soldering iron to create a small hole. The diameter was measured and included in Table 1. The thickness, areal density and resistance were measured. The material was placed in an oven at 175°C for 30 minutes and the shrinkage was measured. Photos were taken, such as Figure 7B shown.
[0089] Example 4
[0090] Aluminized biaxially oriented polyester film was obtained from All Foils Company and is designed for helium filled party balloons. The aluminum coating can retain helium for a longer time, thereby providing a longer lasting loft to the party balloons. The thickness, areal density, and resistance were measured and are shown in Table 1 below. The film was then touched with a hot soldering iron in the same manner as in Example 1. The soldering iron was touched to the current collector to create a small hole. The diameter was measured and included in Table 1. The thickness, areal density, and resistance were measured. The material was placed in an oven at 175°C for 30 minutes and the shrinkage was measured. Photos were taken, as shown in Table 1. Fig. 8A Compared to the commercially available aluminum current collector Comparative Example 1, the material is 65% thinner and 85% lighter, and also dissipates heat, which would have the effect of breaking the internal short circuit in an internally short-circuited lithium-ion battery.
[0091] Example 5
[0092] Dreamweaver Silver 25, a commercially available lithium-ion battery separator, was obtained. It is made from a blend of cellulose with polyacrylonitrile nanofibers and polyester microfibers in a papermaking process and calendered to a low thickness. The separator was then touched with a hot soldering iron in the same manner as in Example 1. No holes were produced by touching the current collector with a thermometer. The thickness, surface density and resistance were measured. The material was placed in an oven at 175°C for 30 minutes and the shrinkage was measured. Compared with prior art comparative examples 3-5, these materials have the following advantages: they do not melt or shrink in the presence of heat and therefore do not shrink in an internally shorted lithium-ion battery to form a larger internal short circuit. As Figure 8B shown.
[0093] Example 6
[0094] Dreamweaver Gold 20, a commercially available prototype lithium-ion battery separator, was obtained. It was made from a blend of cellulose with para-aramid nanofibers and polyester microfibers in a papermaking process and calendered to a low thickness. The separator was then touched with a hot soldering iron in the same manner as in Example 1. Touching the current collector with a thermometer produced no holes. Thickness, surface density and resistance were measured. The material was placed in an oven at 175°C for 30 minutes and the shrinkage was measured. The advantages of this separator compared to the prior art separators are the same as in Example 2.
[0095] Table 1
[0096]
[0097]
[0098] Comparative Example 1-2 is an existing current collector material that exhibits very low resistance, high areal density, and does not react when exposed to a hot soldering iron tip or have any shrinkage at 175°C.
[0099] Examples 1-3 are materials that have infinite resistance, have low areal density, and melt under exposure to 175°C or a hot soldering iron tip. They are excellent substrates for metallization according to the present invention.
[0100] Example 4 is an example of an aluminum-plated polymer film that exhibits moderate resistance, low areal density, and shrinks when exposed to 175°C or a hot soldering iron tip. Examples of potential positive current collector composite films according to the present invention. In practice, and as shown in further examples, it may be desirable to impart higher levels of metal coatings for higher power batteries.
[0101] Examples 5-6 are materials with infinite resistance, low areal density, but very low shrinkage when exposed to 175°C or a hot soldering iron tip. They are examples of polymer substrates of the present invention when the thickness of the metallized coating is thin enough that the metallized coating will degrade under high current conditions associated with short circuits. In addition, cellulose nanofibers and polyester microfibers will oxidize, shrink, and ablate at temperatures far below the melting temperatures of currently practical metal current collectors.
[0102] Example 5 is also made of polyacrylonitrile fibers, which swell when exposed to conventional lithium-ion lithium carbonate electrolytes, which is also an example of a polymer substrate of the present invention, so that the swelling increases under heating and creates cracks in the metallized coating that break the conductive path, thereby improving the safety of the battery by eliminating or greatly reducing the uniform conductive path of the current collector when exposed to heat within the battery.
[0103] Example 7
[0104] The materials used in Example 5 were placed in the deposition position of an MBraun vacuum deposition system using an intermetallic crucible and aluminum pellets. The chamber was evacuated to 3×10 -5 mbar. Increase the power until the aluminum melts, then set the power so that the deposition rate is 3 angstroms / second. Deposition is carried out for 1 hour, and four samples are rotated on the deposition plate. Repeat this process 3 times, so that the total deposition time is 4 hours. The weight, thickness and resistance (DC and 1kHz, 1 inch strip measured between electrodes 1 inch apart) of the sample are measured, and these results are shown in Table 2 below. Point resistance is also measured by using Hioki 3555Battery HiTester at 1kHz and the probe tips are separated by 1 inch. The weight of the added aluminum is obtained by dividing the weight added in the process by the sample area. This is divided by the density of the material to obtain the average thickness of the coating.
[0105] Example 8
[0106] By taking polyethylene terephthalate with a flat cross section and using the process of Tappi T206 to produce 20 g / m 2 The nonwoven polymer substrate was prepared by using a hand sheet of . These hand sheets were then calendered using a 250°F hardened steel roll at 10 m / min and 2000 lbs / in. The material was metallized according to the method of Example 7 and the same measurements were made and recorded in Table 2.
[0107] Example 9
[0108] The material according to Example 5 was deposited according to the method of Example 7, except that the coating was performed at a setting of 5 angstroms / second for 60 minutes. The sample was flipped over and coated on the back side with the same procedure. The surface and cross-section of these materials were imaged under a scanning electron microscope (SEM), and the images are shown in Fig. 9 .
[0109] Example 10
[0110] The material was prepared according to the procedure of Example 9, except that the deposition on each side was only 20 minutes.
[0111] Embodiment 11
[0112] The polymer substrate of Example 8 was prepared except that the sheet was not calendered. Aluminum was deposited at 5 angstroms / second for 20 minutes on each side. Because the material was not calendered, the porosity was very high, resulting in very high resistance values and thin coating weights. Comparison of Example 11 with Example 8 shows the benefit of calendering, which is unexpectedly high.
[0113] Table 2
[0114] sample Increased weight DC resistance 1kHz resistor 1kHz point resistance Average coating thickness unit <![CDATA[g / m 2 ]]> Ohm / □ Ohm / □ Ω Micrometer Example 7 3.5 0.7 0.5 0.1 1.3 Example 8 2.0 7 7 0.4 0.7 Example 9 2.2 0.2 0.8 Example 10 0.8 1.7 0.3 Embodiment 11 0.8 100 0.3
[0115] Example 12
[0116] The aluminum-coated polymer substrate from Example 9 was coated with a mixture of 97% NCM cathode material (NCM523, obtained from BASF), 1% carbon black, and 2% PVDF binder in a solution of N-methyl-2-pyrrolidone. At a thickness of 71 microns, the coating weight was 12.7 mg / cm 2 The material was cut into pieces suitable for 2032 button cells and coated on a copper foil current collector (6 mg / cm 2 , 96.75% graphite (BTR), 0.75% carbon black, 1.5% SBR and 1% CMC) on a graphite negative electrode pair. A single-layer button cell was prepared by placing the negative electrode, separator (Celgard 2320) and NCM coating material into a battery, filling with electrolyte (60uL, 1.0M LiPF6 in EC:DEC:DMC=4:4:2vol+2w.%VC) and sealing the battery by crimping the outer shell. In order to obtain sufficient conductivity, a portion of the aluminum-coated polymer substrate from Example 9 was left uncoated with the positive electrode material and folded to contact the outer shell of the button cell, thereby completing the conductive path. The battery was formed by charging to 4.2V at a constant current of 0.18mA and then charging at a constant voltage (4.2V) until the current dropped to 0.04mA. The battery was cycled three times between 4.2V and 3.0V at a current of 0.37mA, and an average discharge capacity of 1.2mAh was obtained.
[0117] Example 13
[0118] The cell was made according to the procedure and using the materials of Example 12, except that the separator used was Dreamweaver Silver 20. The cell was formed by charging to 4.2 V at a constant current of 0.18 mA, and then charging at a constant voltage (4.2 V) until the current dropped to 0.04 mA. The cell was cycled three times between 4.2 V and 3.0 V at a current of 0.37 mA, and an average discharge capacity of 0.8 mAh was obtained. Thus, in this and previous examples, working rechargeable lithium ion cells were made with an aluminum thickness of less than 1 micron.
[0119] Comparative Example 3
[0120] The aluminum lug (about 2 cm×4 cm) of Comparative Example 1 was connected to the ground of the current source through a metal connector in contact with the entire width of the sample. The voltage limit was set to 4.0 V, and the current limit was set to 1.0 A. A probe connected to a high voltage of the current source was first touched to the metal connector in contact with the entire width of the sample, and then to the aluminum lug several times, thereby creating a short circuit at 1.0 A. The tip of the probe had a length of about 0.25 mm. 2 When contact was made along the entire width, current flowed normally. When the probe first touched the tab, a spark was produced, indicating a very high initial current density. The resulting defects in the current collector sometimes resulted in only holes, while other times there was ablation but the current collector remained intact. In all cases, the circuit remained short-circuited with 1.0 A flowing. Micrographs were taken from ablation defects without holes and are shown in Fig. 10A The experiments were repeated with the current source limits set to 5.0, 3.0, 0.6A, 0.3A and 0.1A, and in all cases the contact was made along the entire width of the current collector and when using a tip size of approximately 0.25mm. 2 When the probe is inserted at the same point, the result is continuous current at the test current limit.
[0121] Comparative Example 4
[0122] A copper tab of similar size from Comparative Example 2 was tested in the same manner as Comparative Example 3. When contact was made across the entire width, current flowed normally. When the probe first touched the tab, sparks were produced, indicating a very high initial current density. The resulting defects in the current collector sometimes resulted in only holes, while at other times there was ablation but the current collector remained intact. In all cases, the circuit remained short-circuited with 0.8A flowing. Micrographs were taken from ablation defects without holes and are shown in Fig. 10AThe experiments were repeated with the current source limits set to 5.0, 3.0, 0.6A, 0.3A and 0.1A, and in all cases the contact was made along the entire width of the current collector and when using a tip size of approximately 0.25mm. 2 When the probe is inserted at the same point, the result is continuous current at the test current limit.
[0123] Embodiment 14
[0124] The inventive aluminum-coated polymer substrate material of Example 7 was tested with similar dimensions using the same method as Comparative Examples 3-4. When contact was made across the entire width, current flowed normally. In each case where the probe directly touched the inventive current collector, far fewer sparks were generated, and the current stopped flowing after the initial spark, leaving an open circuit. In all cases, the final defect was a hole. Micrographs of several examples of holes are shown in Fig.11A and Fig. 11B The experiment was repeated with the current source limits set to 5.0, 3.0, 0.6A, 0.3A and 0.1A, and in all cases the result was continuous current flow when contact was made across the entire width of the current collector, and no current flow through the inventive examples when the probe directly contacted the inventive current collector examples.
[0125] The key invention shown is that when subjected to a short circuit as in Comparative Examples 3-4 and Example 14, for the prior art, the result is a sustained short circuit; while using the materials of the present invention, the result is an open circuit without sustained current flow (i.e., no significant current movement). Therefore, the short circuit of the prior art can and does generate heat, which melts the separator, dissolves the SEI layer and causes thermal runaway of the battery. The open circuit of the current collector of the present invention will not generate heat, thus providing a battery that can withstand an internal short circuit without causing thermal runaway and the smoke, heat and flames generated thereby.
[0126] Examples 15 and 16 and Comparative Examples 5 and 6
[0127] In a roll-to-roll process, two metallized films are made on a 10 micron polyethylene terephthalate film. In this process, the roll of film is placed in a vacuum metallization production machine (an example of which is the Top Met 4450 available from Applied Materials), and the chamber is then evacuated to low pressure. The roll is passed through a heated boat containing molten aluminum at a high speed of, for example, 50 m / min. Above the heated boat containing molten aluminum is a cloud of aluminum smoke, which is deposited on the film, and the deposition rate is controlled by speed and aluminum temperature. A roll of about 500 m long and 70 cm wide is made by multiple passes until the aluminum coating is ~ 300 nm. The coating process is repeated to coat the other side of the film, and the resulting product is used herein as Example 15 ( Figure 4 The current collector of the present invention is a diagram of the current collector used in this example). Therefore, Example 16 (and Figure 5B The diagram represents the current collector used in the structure of the present invention. The basis weight, thickness and conductivity of each film were measured and are reported in Table 3 below. The basis weight of the polyethylene terephthalate film was calculated by subtracting the basis weight of 13.8 g / m 2 Calculate the coating weight by dividing the coating weight by the density of the material (2.7 g / cm for aluminum). 3 , copper is 8.96g / cm 3 ) and assuming it is equal on both sides, to calculate the "Calculated Coating Thickness".
[0128] Comparative Example 5 is a commercially available aluminum foil with a thickness of 17 microns. Comparative Example 6 is a commercially available copper foil with a thickness of 50 microns. Comparative Example 7 is a commercially available copper foil with a thickness of 9 microns.
[0129] Table 3
[0130] sample Basic weight Coating weight thickness DC resistance Calculated coating thickness unit <![CDATA[g / m 2 ]]> Ohm / □ Ohm / □ Ω Micrometer Embodiment 15 17 3 11 0.081 0.5 Example 16 24 10 11 0.041 0.5 Comparative Example 5 46 17 Comparative Example 6 448 50 Comparative Example 7 81 9
[0131] Example 15, Example 16, Comparative Example 5 and Comparative Example 6 were further tested to test their ability to carry very high current densities. A test device was prepared that would contact the current collector film or foil with a polished copper wire having a radius of 0.51 mm (24AWG specification). The tested film or foil was grounded with an aluminum contact that maintained contact with the tested film or foil, and the contact area was greater than 1 square centimeter. The probe was connected in series with a high-power 400W resistor with a resistance of 0.335 ohms and was connected to a Volteq HY3050EX power supply set to control the current. The current collector to be measured was placed in a setup so that the polished wire was in contact with the current collector surface at zero input current. The current was increased in increments of 0.2 amperes, and each increment was maintained for 30 seconds while measuring the voltage across the resistor. When the voltage dropped to zero (indicating that no current was flowing), it was indicated that the sample was faulty. Example 15, Example 16, Comparative Example 5 and Comparative Example 6 were tested separately. Example 15 failed at 7A (average of two measurements). Example 16 failed at 10.2A (average of two measurements). Comparative Examples 5 and 6 both did not fail below 20A. Both Example 15 and Example 16 showed holes in the current collector with a radius greater than 1 mm, while neither Comparative Examples 5 or 6 showed any damage to the foil. In this example test, it is advantageous to have a current collector that cannot carry a current greater than 20A, or preferably greater than 15A, or more preferably greater than 12A.
[0132] In another test designed to simulate the use of these inventive current collectors as tabs connecting the electrode stack of a battery to an electronic device in use (inside or outside the battery), Examples 15 and 16 and Comparative Examples 5 and 6 were tested for current capacity along the strip. To prepare the samples for testing, the current collectors were cut into Fig.12 The shape shown, which consists of a strip of material 4 centimeters by 1 centimeter (4cm×1cm), the end of the strip ending in a truncated right isosceles triangle with a side length of 4cm. Each triangle of the test piece is contacted by an aluminum part with a contact surface area greater than 1cm. One side is connected through a 400W 0.335 ohm resistor, and the circuit is connected to a Volteq HY3050EX power supply. The voltage is measured along the resistor to measure the current, and the part shows failure when this voltage drops to zero. For each test, the part is connected to a power supply set to zero current, then increased in increments of 0.2A and left at each new voltage for 30 seconds until the part fails and the current drops to zero. The test is configured so that the metallized current collector can be measured with one or both sides of the metallized current collector in contact. The failure current is shown in Table 4 below. For materials tested in 4 cm x 1 cm strips, it is advantageous to provide an internal fuse by limiting the amount of current that can flow to less than 20 A, or preferably less than 15 A, or more preferably less than 10 A, respectively, each with single or double sided contacts.
[0133] Table 4
[0134] sample Single-side fault voltage Single-side fault voltage unit V V Embodiment 15 2.7 4.5 Example 16 24 10 Comparative Example 5 No fault below 20A No fault below 20A Comparative Example 6 No fault below 20A No fault below 20A
[0135] Examples 17-19 and Comparative Example 8
[0136] The cells were fabricated by coating the standard foil current collectors and the metallized PET film current collectors from Examples 15 and 16 with the electrode materials. The NMC 523 cathode material was prepared using BASF NMC523 (97%), carbon black (2%), and PVDF (1%) in NMP solvent and at a basis weight of 220 g / m2 (corresponding to 3.3 mAh / cm 2 The cathode loading density was 118 g / m 2 and coated on an aluminum current collector (15 μm aluminum current collector) and Example 15. The negative electrode material was prepared using graphite BTR-918S (94%), carbon black (5%) and PVDF (1%) in NMP solvent and 2 The rate (corresponding to 4.0 mAh / cm 2The negative electrode loading density of 1000 μm was coated on a copper current collector (18 micron copper current collector). Four double-sided positive electrodes were prepared, as well as three double-sided negative electrodes and two single-sided negative electrodes. They were stacked together with Celgard 2500 separators to form small soft-pack batteries, which were then filled with electrolyte and sealed with a design capacity of 1Ah. Four types of batteries were made by different combinations of foil materials, and the capacitance was measured at C / 10 and C / 5 (i.e., 0.1A and 0.2A). The battery was formed by charging to 4.2V at 100mA and kept at 4.2V until the current dropped to 10mA. The fully formed battery was then weighed, and the capacity was tested by discharging at C / 10, then charging at C / 10 and discharging at C / 5. These results are shown in Table 5 below.
[0137] Table 5
[0138] sample Positive current collector Negative current collector Battery weight C / 10 Capacity C / 5 Capacity unit gram mAh mAh Comparative Example 8 Al Foil Cu Foil 27 924 615 Embodiment 17 Embodiment 15 Cu Foil 26.8 1049 751 Embodiment 18 Al Foil Example 16 24.7 1096 853 Embodiment 19 Embodiment 15 Example 16 24.7 1057 848
[0139] Thus, it has been shown that the embodiments provided above exhibit desirable thickness, metal coating, and conductivity results required to prevent thermal runaway within an electrolyte-containing cell, thereby providing not only a safer and more reliable type, but also a type that requires far less internal weight components than before without sacrificing safety (but in fact improving upon this).
[0140] Although the present invention has been described in detail, it will be apparent to those skilled in the art that variations and modifications will be possible without departing from the scope of the present invention. Therefore, the scope of the present invention should be determined only by the appended claims.
[0141] Although the present invention has been described in detail, it will be apparent to those skilled in the art that variations and modifications will be possible without departing from the scope of the present invention. Therefore, the scope of the present invention should be determined only by the appended claims.
[0142] One aspect of the technology of the present invention is a method or process for manufacturing an energy storage device, which includes the following steps: providing an electrode having at least one metallized substrate coated with an ion storage material; providing a counter electrode; stacking the electrode and the counter electrode relative to each other and inserting a diaphragm assembly between the electrode and the counter electrode; providing a packaging material including an electrical contact assembly, wherein the contact includes a portion present inside the packaging material and a portion present outside the packaging material; electrically connecting the electrical contact to the metallized substrate; introducing at least one liquid electrolyte with ions into the interior of the packaging material; and sealing the packaging material.
[0143] The implementation method of the technology of the present invention is: the energy storage device can be a lithium-ion battery.
[0144] Some embodiments of the present technology include: the metallized substrate can be a current collector comprising a film having at least one metal coating, and the total thickness of the current collector is less than 20 microns. The metal can be a transition metal, such as but not limited to copper or aluminum.
[0145] Some embodiments of the present technology may have an overall areal density of less than 50 grams per square meter.
[0146] Embodiments of the present technology may have a resistance of at least one side of the metallized substrate greater than 5 milliohms / square and less than 1 ohm / square, and a coating thickness less than 5 microns.
[0147] Some embodiments of the present technology may have a membrane configured to not rupture below 200°C and exhibit less than 10% shrinkage before 200°C when exposed to the shrinkage test described in Section 3.5 of NASA TM-2010-216099.
[0148] Embodiments of the present technology may have an electrolyte comprising an organic solvent.
[0149] Some embodiments of the present technology may provide a separator having a polymer structure, a ceramic structure, or a non-woven fabric structure.
[0150] Some embodiments of the present technology may have ion storage materials coated on both sides of a metallized substrate.
[0151] Embodiments of the present technology may have electrical connections between electrical contacts and metallized substrates with surface areas greater than 1 square millimeter.
[0152] Although the embodiments of the lithium energy storage device with internal fuse have been described in detail, it is obvious that modifications and variations can be made thereto, all of which fall within the true spirit and scope of the invention. Then, with respect to the above description, it should be recognized that the optimal dimensional relationships of the components of the present invention, including changes in size, material, shape, form, function and mode of operation, assembly and use are considered to be obvious to those skilled in the art, and all equivalent relationships to those shown in the drawings and described in the specification are intended to be covered by the present invention technology.
[0153] Therefore, the foregoing is considered to be only illustrative of the principles of the present invention. In addition, since many modifications and changes will be readily apparent to those skilled in the art, it is not desirable to limit the present invention to the exact configuration and operation shown and described, so all suitable modifications and equivalents may be adopted within the scope of the present invention.
Claims
1. An energy storage device, comprising: A negative electrode, a positive electrode, at least one separator interposed between the negative electrode and the positive electrode, at least one liquid electrolyte, and at least one current collector in contact with at least one of the negative electrode and the positive electrode, wherein the at least one current collector has a top surface and a bottom surface and comprises a metal-coated polymer substrate, the metal-coated polymer substrate being a polymer substrate coated with a conductive metal on both surfaces; wherein the at least one separator has a polymer structure, a ceramic structure or a non-woven structure; wherein the metal-coated polymer substrate exhibits a strength of less than 40 g / m 2 The metal-coated polymer substrate has an area density of less than 20 microns and a resistance measurement value of less than 1 ohm / □; wherein said at least one current collector further exhibits the ability to carry current density when operating normally along a horizontal current path and further exhibits the ability to immediately stop current flow during and at the location of a short circuit and thereafter remain viable as a current collector; and Wherein, when subjected to the shrinkage test described in Section 3.5 of NASATM-2010-216099, the at least one separator exhibits no fracture in the separator when exposed to a temperature of 180°C and no shrinkage of more than 20% at 180°C.
2. The energy storage device according to claim 1, wherein: The conductive metal is selected from the group consisting of aluminum, copper, gold, silver, vanadium, rubidium, iridium, indium, platinum, and any combination and alloy thereof.
3. The energy storage device according to claim 1, wherein: The polymer substrate exhibited a porosity of up to 60%.
Citation Information
Patent Citations
Current collector and nonaqueous secondary cell
CN102891323A